Chemisorption of Lewis Bases on Zeolites – A New Interpretation of the Results - L.K. Patrylak (Adsorption Science & Technology)
The chemisorption of pyridine, the 2,2,6,6-tetramethyl-4-oxypiperidine-1-oxyl radical and ammonia on the cationized and decationized forms of X and Y zeolites, as used for the determination of BrSnsted and Lewis acidity using infrared spectroscopy, ESR spectroscopy and the temperature programmed desorption of ammonia, has been investigated. A new approach, based on a detailed quantitative analysis of the experimental data, is proposed. It was found that the sodium cations are not the Lewis acid sites, but that on the outer surface of zeolite crystals such sites correspond to coordinatively unsaturated aluminium atoms. These amount to 17% and 14%, respectively, of the entire surface aluminium for NaX and NaY zeolites. The remaining coordinatively unsaturated aluminium in the heart of a zeolite structure decationized to 84% make little contribution to the overall percentage. It was shown that the temperature programmed desorption of ammonia is the most effective method for providing a quantitative determination of the BrOnsted acidity of zeolites. The overwhelming majority of Lewis acid sites on zeolites whose sodium ions had been exchanged for di- and tri-valent cations was provided by these latter cations. The quantitative accuracy of the determination of Lewis acid sites was not noticeably affected by the presence of BrOnsted sites on the zeolite.